An exploration of aspects of the South African Bill of Rights through applied drama amongst young adults (care givers) at Rena Le Lona Creative Centre for Children, Johannesburg South Africa - Apotieri-Abdulai, Oluwadamilola (My University, 2016)
This research report evaluates an exploration of how Applied Drama methods can aid the pedagogy of Human Rights and encourage an attitude of responsibility towards human rights among young adult caregivers at the Rena la Lona Creative Centre in Soweto, South Africa. Human Rights are basic standards which inform the standard of living among people so that they live in dignity. In the context of this study, Human rights education through Applied Drama methods is the means through which people are empowered and are given a sense for responsibility. The study consisted of the use of Applied Drama methods to articulate the education of equality and Human rights. This was done through a practice-based research framework wherein the research is informed by collective practice and also relies on theoretical findings. The first chapter articulates the background and justification of study. Chapter two focuses on the literature and methodology that inform the study. Chapter three explores the research findings through an analysis of the methods used and the learning derived from the practice. Chapter four concludes with the reflection around the research results. The conclusion asserts that the explored Applied Drama methods can be used as a tool for holistic education of the South African Bill of Rights within an informal education setting such as the Rena la Lona Creative Centre.
A research report submitted to the Drama for Life division of Wits School of Arts, Faculty of Humanities, for the award of the degree of Masters in Applied Drama at University of the Witwatersrand, 2015
Keywords: Theater--Political aspects; Theater and society; Drama in education; Drama--Therapeutic use